Pedagogical Integration of Traffic Parks: Contextual Learning Resources for Early Childhood Education - Fachrul Rozie; Evie Palenewen; Effendi Limbong; Gisela Silvania Algazira; Zerliyana Luthfiyawati Fazry; Zulkarnain Ramli (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study investigates how the Karang Anyar Traffic Park in Samarinda, Indonesia, can be integrated pedagogically as a contextual learning resource in Early Childhood Education (ECE). It addresses the gap between public Child-Friendly City policies and the actual pedagogical utilization of specific thematic urban spaces to foster safety awareness and self-regulation in early childhood. Design/methods/approach – A qualitative case study design was employed. Data were collected over a three-month period (August–October 2024) through multi-perspective interviews with a village head, park managers, ECE principals, and teachers, alongside field observations and institutional documentation. The data were analyzed using Braun & Clarke’s thematic analysis framework. Findings – The thematic analysis yielded five interconnected themes demonstrating that the traffic park serves as an effective